A Study of Program Evaluation: Community Information Group - A Triangle of Information, Government and Community - Rachmawati, Tutik; Junio, Laurel Laras (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
This paper discusses a program evaluation study on Community Information Group. It is a program that is established by the Ministry of Communication and Information, which is based on the Ministerial Decree No. 8/2010. Through the program, the government is expected to disseminate public information and, simultaneously, the community will be able to voice their concerns and needs. This research used an exploratory survey with a sequential exploratory. In the qualitative analysis, we interviewed 15 key persons to understand the nature of the program and the impact of the access to information. This is enriched with a quantitative analysis. A closed-ended questionnaire was used to survey 62 respondents. The evaluation method was randomized post-test only group design. This research utilized a case study of research design with the Community Information Group of Sukabungah Village - Bandung, because it is regarded as one of the best practices of CommunityInformation Group in Bandung City. Furthermore, Sukagalih Village was used as the control group of the evaluation program study. Dolbeare's model of policy impact was also used in this research. We constructed a causal logic of the program to fully understand the program itself. It is evident from the findings that a set of activities in this program did not meet its expectedimpact. Further, even though the activities are useful for the citizens, the citizens already had access to the same activities provided by other programs. It can be concluded that the establishment of the Community Information Group is inefficient. Hence the Community Information Group program should be re-designed to maximize the impact or otherwise be terminated.